2003
DOI: 10.1074/jbc.m302421200
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of Myc as a Potential Target for Growth Arrest Induced by Human Polynucleotide Phosphorylase (hPNPase) in Human Melanoma Cells

Abstract: Terminal differentiation and senescence share several common properties, including irreversible cessation of growth and changes in gene expression profiles. To identify molecules that converge in both processes, an overlapping pathway screening was employed that identified old-35, which is human polynucleotide phosphorylase (hPNPase old-35 ), a 3,5-exoribonuclease. We previously demonstrated that hPNPase old-35 is a type I interferon-inducible gene that is also induced in senescent fibroblasts. In vitro RNA de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
112
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(116 citation statements)
references
References 65 publications
(45 reference statements)
4
112
0
Order By: Relevance
“…6 Moreover, hPNPase old-35 induces gene expression changes that are consistent with G 1 cell cycle arrest, such as downregulation of c-myc, upregulation of p27 KIP-1 and hypophosphorylation of Rb. 6 We previously found that downregulation of c-myc plays a critical part in hPNPase old-35 -induced growth inhibition, since overexpression of c-myc partially but significantly ablated this growth-inhibitory effect. 6,9 In vitro mRNA degradation assays revealed that, as an exoribonuclease, hPNPase old-35 directly and specifically degraded c-myc mRNA.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…6 Moreover, hPNPase old-35 induces gene expression changes that are consistent with G 1 cell cycle arrest, such as downregulation of c-myc, upregulation of p27 KIP-1 and hypophosphorylation of Rb. 6 We previously found that downregulation of c-myc plays a critical part in hPNPase old-35 -induced growth inhibition, since overexpression of c-myc partially but significantly ablated this growth-inhibitory effect. 6,9 In vitro mRNA degradation assays revealed that, as an exoribonuclease, hPNPase old-35 directly and specifically degraded c-myc mRNA.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Biochemically, hPNPase old-35 is a 3 0 ,5 0 exoribonuclease catalyzing mRNA decay in a 3 0 -5 0 direction. 3 Polynucleotide phosphorylase (PNPase) is an evolutionary conserved gene and the bacterial and plant enzymes have been cloned and extensively studied for decades.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Part of the PNPase population in E. coli is associated with the endoribonuclease RNase E, an RNA helicase, enolase, and possibly other proteins in a highmolecular weight complex called the degradosome [10][11][12][13][14]. Human PNPase was identified in an overlapping pathway screen to discover genes displaying coordinated expression as a consequence of terminal differentiation and senescence of melanoma cells [15][16][17]. In human cells PNPase is mostly located in the mitochondrial intermembrane space and may not play the major role in the processing and degradation of RNA that it plays in bacteria, chloroplasts and plant mitochondria [18,19].…”
mentioning
confidence: 99%